2016
DOI: 10.4103/2347-5625.189810
|View full text |Cite
|
Sign up to set email alerts
|

The effect of complementary therapy for hospital nurses with high stress

Abstract: Objective:This study was to examine the effect of complementary therapy (CT) for nurses with high stress levels. It was taken before we employ this technique for cancer survivors because cancer patients are a heterogeneous group that requires substantial resources to investigate.Methods:A quasi-experimental design with five groups was employed for this study. The groups were examined whether there were effects for reducing the stress and the differences in effectiveness among four intervention groups and a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Nineteen studies provided some form of active intervention. Interventions used in these RCT studies were based on education (mostly stress coping, n = 15) [55][56][57][58][59]65,77,79,91,92,94,100,101,108,111], PA (n = 10) [115,118,120,122,124,125,[128][129][130][131], relaxation (n = 8) [167,169,170,[172][173][174][175][176], meditation/mindfulness (n = 6) [150,155,157,161,165,166], alternative approaches (n = 5) [182][183][184][185]190], diet (n = 2) [139,140], smoking cessation (n = 1) [141], and finally seven used multi-component complex interventions that included more than one element (e....…”
Section: Results Of Included Rctsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies provided some form of active intervention. Interventions used in these RCT studies were based on education (mostly stress coping, n = 15) [55][56][57][58][59]65,77,79,91,92,94,100,101,108,111], PA (n = 10) [115,118,120,122,124,125,[128][129][130][131], relaxation (n = 8) [167,169,170,[172][173][174][175][176], meditation/mindfulness (n = 6) [150,155,157,161,165,166], alternative approaches (n = 5) [182][183][184][185]190], diet (n = 2) [139,140], smoking cessation (n = 1) [141], and finally seven used multi-component complex interventions that included more than one element (e....…”
Section: Results Of Included Rctsmentioning
confidence: 99%
“…A significant decrease in depression and/or anxiety was reported in 19 studies (six studies reported decrease in solely depressive symptoms [60,93,97,118,139,177], seven in solely anxiety [164,169,171,174,178,182,187], and six in both depression and anxiety [95,143,156,157,172,176]). Of the 19 studies reporting improvements in depression and/or anxiety, 10 were RCTs [60,118,139,157,169,172,174,176,178,182], two were controlled studies [93,177] and seven were uncontrolled studies [95,97,143,156,164,171,187]. In two studies measuring both depressive symptoms and anxiety [97,139], depressive symptoms improved but anxiety did not.…”
Section: Depression and Anxietymentioning
confidence: 95%
See 2 more Smart Citations
“…Interventions that lead to a significant reduction of stress are based on mindfulness/meditation techniques [85], educational approaches like stress and coping behavior techniques [86], light therapy [87], or physical activities like yoga or walking. Depression and anxiety can be significantly reduced by the mindfulness-based cognitive therapy [88] or education-based interventions [89] or relaxation methods (e.g., feet bath [90], music [90], music-based relaxation [91]).…”
Section: Discussionmentioning
confidence: 99%